Battery

By using a nonaqueous electrolyte with high concentration of lithium salt and a cross-linked modified rubber termination layer in the battery, the safety hazards of the battery at high temperatures are solved, and the battery's high temperature performance is improved and the battery life is extended.

CN119153756APending Publication Date: 2024-12-17ZHUHAI COSMX BATTERY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411287381.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2021-11-23
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing batteries are prone to safety accidents in high temperature environments, such as battery cells deforming, ignition or explosion. The main reason is that the electrode sheet termination tape loses adhesion under high temperature and high pressure and the electrolyte decomposes under high temperature and high voltage, resulting in deterioration of battery cells. .

Method used

Using a nonaqueous electrolyte with high concentration of lithium salt and a crosslinked modified rubber termination layer is set in the positive electrode sheet termination tape to form a specific three-dimensional network structure, which enhances the resistance to multiple flexurality and adhesion of the rubber layer to prevent The glue layer overflows and the battery cell deforms, while forming a solid electrode/electrolyte interface mask at the positive and negative electrode interface.

Benefits of technology

It significantly improves the safety performance of the battery at high temperatures, delays the aging of the positive electrode sheet termination tape, avoids the problem of edge lithium during cell deformation and circulation, and improves the life and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153756A_ABST
    Figure CN119153756A_ABST
Patent Text Reader

Abstract

The invention provides a battery. According to the battery, through the synergistic effect of the positive plate termination adhesive tape and the concentration of the lithium salt in the non-aqueous electrolyte, the high-temperature performance of the battery cell of the prepared battery can be effectively improved, and meanwhile, the problem that lithium is separated out from the edge of a pole plate after the battery cell circulates can be solved; the problems that when the battery is used in a high-temperature environment, the positive plate termination adhesive tape warps and deforms, so that the high-temperature storage thickness of a battery cell is invalid, high-temperature circulation lithium precipitation is caused, an adhesive layer in the positive plate termination adhesive tape is easily dissolved in non-aqueous electrolyte, and the non-aqueous electrolyte is easily oxidized, reduced and decomposed on a positive electrode interface and a negative electrode interface are solved.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This disclosure is a divisional application of the invention patent application with application number 202111394913.2 submitted to the China Patent Office, application date November 23, 2021, and invention name “A Battery”. Technical Field

[0002] The present invention belongs to the technical field of batteries, and in particular relates to a high-voltage battery with excellent high-temperature performance. Background Art

[0003] In recent years, batteries have been widely used in smart phones, tablets, smart wearables, power tools, electric vehicles, etc. With the widespread use of batteries, consumers' requirements for battery energy density and usage environment are constantly increasing, which requires batteries to have excellent high-temperature safety performance at high voltage.

[0004] At present, there are safety hazards in the use of batteries. For example, when the battery is in some extreme use conditions such as continuous high temperature, serious safety accidents are prone to occur, and the battery cell is deformed, caught fire or even exploded. The main reason for these problems is that the adhesive layer of the battery pole termination tape is easily dissolved in the electrolyte under high temperature and high pressure and loses its adhesiveness, making the tape unable to play an effective fixing role, resulting in local deformation and warping of the battery cell or short circuit causing safety accidents; on the other hand, the electrolyte is easy to decompose under high temperature and high voltage, and redox decomposition occurs on the surface of the positive and negative electrodes to destroy the SEI film, causing the battery cell impedance to continue to increase and deteriorate the battery cell performance. Summary of the invention

[0005] The purpose of the present invention is to solve the problems of the positive electrode termination tape warping and deformation when the existing battery is used in a high temperature environment, resulting in high temperature storage thickness failure of the battery cell and high temperature cycle lithium precipitation, the adhesive layer in the positive electrode termination tape being easily soluble in the non-aqueous electrolyte, and the non-aqueous electrolyte being easily oxidized and reduced and decomposed at the positive and negative electrode interfaces, and to provide a battery which is a high voltage battery and has excellent high temperature performance.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] A battery, comprising a positive electrode sheet, a negative electrode sheet, a non-aqueous electrolyte and a separator; a positive electrode sheet termination tape is arranged at the paste tail of the positive electrode sheet; the non-aqueous electrolyte comprises a non-aqueous organic solvent and a lithium salt;

[0008] The area of ​​the positive electrode termination tape is A cm 2 , the concentration of the lithium salt is B mol / L, the width of the positive electrode sheet is C cm, wherein the ratio of A to B is in the range of 2 to 20; the ratio of A to C is in the range of 1 to 3.

[0009] In the battery, the number of positive electrode sheet termination tapes is two, that is, one positive electrode sheet termination tape is disposed on both sides of the positive electrode current collector in the positive electrode sheet, and the area A of the positive electrode sheet termination tape refers to the area of ​​the positive electrode sheet termination tape disposed on one side of the positive electrode current collector in the positive electrode sheet. Furthermore, the areas of the positive electrode sheet termination tapes disposed on both sides of the positive electrode current collector in the positive electrode sheet are the same.

[0010] According to the present invention, the ratio of A to B is 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or any point value in the range formed by the two end points mentioned above. When the ratio of A to B is between 2 and 20, the high concentration of lithium salt in the non-aqueous electrolyte and the positive electrode termination tape can have a better synergistic effect; specifically, the high concentration of solute lithium salt is more conducive to enhancing the interaction between the solute and the solvent in the solution, and the free solvent molecules disappear to form a new non-aqueous electrolyte, that is, a high concentration non-aqueous electrolyte. At the current ratio, it is more conducive to the formation of a specific three-dimensional network structure of the non-aqueous electrolyte, and ions (such as lithium ions) form coordination with limited free solvent molecules and anions, which is significantly different from the free solvent molecules. The conventional low-concentration electrolyte with the positive electrode termination tape as the main body can better slow down the aging of the glue layer in the positive electrode termination tape after the positive electrode termination tape is immersed in the non-aqueous electrolyte, so that it still maintains good resistance to multiple flexures and adhesion, ensures that the tensile strength is still maintained under immersion in the non-aqueous electrolyte, delays the aging failure of the positive electrode termination tape, avoids the glue layer overflowing from the positive electrode termination tape and covering the surface of the positive electrode active material to cause pore blockage, improves the deformation of the battery cell caused by the warping of the positive electrode termination tape, and at the same time improves the problem of edge lithium plating caused by pore blockage during the battery cell cycle.

[0011] According to the present invention, the ratio of A to C is 1, 1.2, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.5, 3 or any point value within the range formed by the two end points. When the ratio of A to C is between 1 and 3, the glue layer area of ​​the positive electrode termination tape more reasonably covers the surface of the paste and the blank foil to reduce the influence of the electrolyte on the glue layer.

[0012] According to the present invention, a positive electrode termination tape is arranged at the paste tail of the positive electrode sheet, and the arrangement of the positive electrode termination tape can also fix the tail of the battery cell and cover the burrs of the cut edge of the positive electrode sheet to prevent the battery from short circuit and play a role of insulation protection.

[0013] According to the present invention, the area A of the positive electrode termination tape is 3 cm 2 ~120cm 2 Range; Exemplarily, the area A of the positive electrode termination tape is 3cm 2 , 5cm 2 , 10cm2 , 20cm 2 、30cm 2 、40cm 2 , 50cm 2 、60cm 2 、70cm 2 、80cm 2 、90cm 2 、100cm 2 、120cm 2 Or any point value within the range formed by the two endpoints mentioned above.

[0014] According to the present invention, the width C of the positive electrode sheet is between 1 cm and 120 cm; illustratively, the width C of the positive electrode sheet is 1 cm, 3 cm, 5 cm, 6 cm, 8 cm, 10 cm, 16 cm, 20 cm, 30 cm, 40 cm, 50 cm, 60 cm, 70 cm, 80 cm, 90 cm, 100 cm, 110 cm, 120 cm or any point value within the range formed by two end points.

[0015] According to the present invention, the positive electrode sheet termination tape comprises a PET substrate and a rubber termination layer coated on the surface of the PET substrate.

[0016] According to the present invention, the thickness of the positive electrode termination tape is 8 μm to 20 μm.

[0017] According to the present invention, the rubber termination layer comprises a cross-linked modified rubber.

[0018] According to the present invention, the crosslinking agent of the crosslinked modified rubber includes vinylene carbonate.

[0019] According to the present invention, the rubber of the cross-linked modified rubber is selected from at least one of natural rubber, styrene-butadiene rubber, polyisobutylene rubber, butyl rubber, nitrile rubber and the like.

[0020] According to the present invention, the content of vinylene carbonate accounts for 0.5-5wt.% of the mass of the cross-linked modified rubber, for example, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.2wt%, 1.5wt%, 1.8wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 3.8wt%, 4wt%, 4.5wt% or 5wt%.

[0021] According to the present invention, the cross-linked modified rubber further comprises an auxiliary agent, and the auxiliary agent is, for example, at least one selected from antioxidants, inorganic fillers and the like.

[0022] According to the present invention, the antioxidant is a conventionally used antioxidant suitable for crosslinking and modifying rubber.

[0023] According to the present invention, the inorganic filler is a conventionally used inorganic filler suitable for crosslinking and modifying rubber.

[0024] According to the present invention, the concentration of the lithium salt is the molar percentage of the lithium salt in the non-aqueous electrolyte (in mol / L).

[0025] According to the present invention, the concentration B of the lithium salt is 1 mol / L to 6 mol / L; preferably, the concentration B of the lithium salt is 1.5 mol / L to 3 mol / L; for example, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 5 mol / L or 6 mol / L.

[0026] According to the present invention, the electrolyte additive also includes at least one of 1,3-propane sultone, 1,3-propylene sultone, fluoroethylene carbonate, vinyl sulfite, vinyl sulfate, lithium dioxalatoborate, lithium difluorophosphate, lithium difluorooxalatophosphate and vinyl vinyl carbonate, and its content accounts for 0 to 10 wt% of the total mass of the non-aqueous electrolyte.

[0027] According to the present invention, the non-aqueous organic solvent is selected from at least one of carbonates, carboxylates and fluoroethers, wherein the carbonate is selected from one or more combinations of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate and methyl propyl carbonate; the carboxylates are selected from one or more combinations of ethyl propionate and propyl propionate; and the fluoroether is selected from 1,1,2,3-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0028] According to the present invention, the lithium salt is selected from at least one of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate.

[0029] According to the present invention, the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer coated on one or both sides of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, a conductive agent and a binder.

[0030] The positive electrode active material is selected from lithium cobalt oxide or lithium cobalt oxide doped with or coated with two or more elements selected from Al, Mg, Mn, Cr, Ti, and Zr. The chemical formula of the lithium cobalt oxide doped with or coated with two or more elements selected from Al, Mg, Mn, Cr, Ti, and Zr is Li x Co 1-y1-y2-y3-y4 A y1 B y2 C y3 D y4O2; 0.95≤x≤1.05, 0.01≤y1≤0.1, 0.01≤y2≤0.1, 0≤y3≤0.1, 0≤y4≤0.1, A, B, C, D are selected from two or more elements of Al, Mg, Mn, Cr, Ti, Zr.

[0031] According to the present invention, the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer coated on one side or both sides of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, a conductive agent and a binder.

[0032] The negative electrode active material is selected from graphite or a graphite composite material containing 1-12wt% SiOx / C or Si / C.

[0033] According to the present invention, the charging cut-off voltage of the battery is 4.45V or above.

[0034] According to the present invention, the battery is a lithium-ion battery.

[0035] In the present invention, the term "in the range of..." includes endpoint values. For example, "in the range of 2 to 20" means greater than or equal to 2 and less than or equal to 20.

[0036] The beneficial effects of the present invention are:

[0037] The present invention provides a battery, which is a high-voltage battery and has excellent high-temperature performance. The inventor of the present invention has found through intensive research that the high-temperature performance of the prepared battery cell can be effectively improved through the synergistic effect of the positive electrode termination tape and the non-aqueous electrolyte, and at the same time, the problem of lithium deposition at the edge of the electrode after the battery cell cycle can be solved, and the problem of the positive electrode termination tape warping and deformation when the battery is used in a high-temperature environment, resulting in failure of the high-temperature storage thickness of the battery cell and lithium deposition during high-temperature cycles, the adhesive layer in the positive electrode termination tape being easily soluble in the non-aqueous electrolyte, and the non-aqueous electrolyte being easily oxidized and reduced at the interface of the positive and negative electrodes can be avoided.

[0038] Specifically, a high concentration of solute lithium salt is more conducive to enhancing the interaction between the solute and the solvent in the solution, and the free solvent molecules disappear to form a new non-aqueous electrolyte, namely a high-concentration non-aqueous electrolyte. At the current ratio, it is more conducive to the formation of a specific three-dimensional network structure of the non-aqueous electrolyte. Ions (such as lithium ions) form coordination with limited free solvent molecules and anions, which is significantly different from the conventional low-concentration electrolyte with free solvent molecules as the main body. It can inhibit the electrolyte from soaking into the tape, so that the rubber termination layer maintains better viscosity and is more stable. The liquefaction and fluidity can be reduced, and the aging of the rubber termination tape after the positive electrode termination tape is immersed in the non-aqueous electrolyte can be better slowed down, so that it can still maintain good resistance to multiple flexures and adhesion, ensure that it still maintains a certain tensile strength when immersed in the non-aqueous electrolyte, delay the aging failure of the positive electrode termination tape, avoid the rubber termination tape overflowing from the positive electrode termination tape and covering the surface of the positive electrode active material to cause pore blockage, improve the deformation of the battery cell caused by the warping of the positive electrode termination tape, and at the same time improve the edge lithium plating caused by pore blockage during the battery cell cycle.

[0039] Furthermore, as the lithium salt concentration increases, the operating voltage range of the non-aqueous electrolyte becomes wider, matching the high-voltage positive electrode material to achieve stable charging and discharging. The fewer flammable solvent molecules can alleviate the reaction between the electrolyte and the active oxygen generated by the positive electrode, thereby improving the battery life and safety.

[0040] Furthermore, the additives in the non-aqueous electrolyte can also form a strong electrode / electrolyte interface film on the surface of the positive and negative electrodes, optimize the embedding / ejection of ions on the surface of the positive and negative electrodes, and improve the cycle performance of the battery.

[0041] Furthermore, the rubber termination layer in the positive termination tape contains vinylene carbonate, which can participate in the cross-linking polymerization of rubber to prevent cracking, making the rubber termination layer more resistant to high temperature and high pressure, stabilizing the structure of the layer, and further improving the high temperature performance of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a schematic structural diagram of a positive electrode sheet according to a preferred embodiment of the present invention.

[0043] Figure 2 This is a schematic structural diagram of a positive electrode sheet according to another preferred embodiment of the present invention.

[0044] Figure 3 for Figure 2 A side view of the positive electrode sheet.

[0045] Figure markings: 1—head of positive electrode sheet; 2—tail of positive electrode sheet; 3—empty foil area; 4—termination tape of positive electrode sheet; 5—tail of positive electrode sheet on one side; 6—termination tape of positive electrode sheet on one side; 7—tail of positive electrode sheet on the other side; 8—termination tape of positive electrode sheet on the other side. DETAILED DESCRIPTION

[0046] In the present invention, the "positive electrode sheet termination tape" refers to a tape arranged at the tail of the paste (such as the positive electrode active material layer) on the surface of the positive electrode collector in the positive electrode sheet, wherein a portion of the positive electrode sheet termination tape covers the paste on the surface of the positive electrode collector, and a portion of the positive electrode sheet termination tape covers the surface of the positive electrode collector (i.e., the empty foil on the surface of the positive electrode collector), as shown in the specific example. Figure 1 to Figure 3 shown.

[0047] The present invention will be described in further detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0048] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0049] Comparative Examples 1-5 and Examples 1-7

[0050] The lithium-ion batteries of Comparative Examples 1-5 and Examples 1-7 were all prepared according to the following preparation method, with the only difference being the positive electrode termination tape at the tail of the positive electrode paste and the non-aqueous electrolyte. The specific differences are shown in Table 1.

[0051] (1) Preparation of positive electrode

[0052] The positive electrode active material LiCoO2, the binder polyvinylidene fluoride (PVDF), and the conductive agent acetylene black are mixed in a weight ratio of 97.2:1.3:1.5, and N-methylpyrrolidone (NMP) is added, and stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode slurry with uniform fluidity; the positive electrode slurry is evenly coated on an aluminum foil with a thickness of 9 to 12 μm; the coated aluminum foil is baked in an oven with 5 different temperature gradients, and then dried in an oven at 120°C for 8 hours, and then rolled and cut to obtain the required positive electrode sheets of different sizes. The specific electrode sheet widths are shown in Table 1.

[0053] (2) Negative electrode preparation

[0054] 96.5% by mass of artificial graphite negative electrode material, 0.1% by mass of single-walled carbon nanotube (SWCNT) conductive agent, 1% by mass of conductive carbon black (SP) conductive agent, 1% by mass of sodium carboxymethyl cellulose (CMC) binder and 1.4% by mass of styrene-butadiene rubber (SBR) binder were made into slurry by a wet process, coated on the surface of the negative electrode current collector copper foil, and dried (temperature: 85°C, time: 5h), rolled and die-cut to obtain negative electrode sheets of different sizes.

[0055] (3) Preparation of non-aqueous electrolyte

[0056] In a glove box filled with argon (water <10ppm, oxygen <1ppm), ethylene carbonate (EC), propylene carbonate (PC), propyl propionate (PP), and 1,1,2,3-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether were mixed in a mass ratio of 2:1:3:2, and lithium salt (the specific amount and selection of lithium salt are shown in Table 1) was slowly added to the mixed solution, and stirred evenly to obtain a non-aqueous electrolyte.

[0057] (4) Preparation of diaphragm

[0058] A polyethylene diaphragm with a thickness of 7 to 9 μm is selected.

[0059] (5) Preparation of positive electrode termination tape

[0060] 82 parts by weight of natural rubber, 24 parts by weight of styrene-butadiene rubber, 20 parts by weight of butyl rubber, 10 parts by weight of nitrile rubber, 28 parts by weight of terpene resin, and 16 parts by weight of antioxidant are sequentially added to 1500 parts by weight of a mixed solvent (ethyl acetate, toluene, and xylene in a mass ratio of 1:1:1), stirred evenly at 85°C to obtain a mixed solution, 105 parts by weight of polyisobutylene rubber and 38 parts by weight of inorganic pigment are sequentially added to the mixed solution, stirred evenly at 80°C to further obtain a mixed solution, and then a certain weight portion of cross-linking agent vinylene carbonate is added to the mixed solution, stirred evenly at room temperature, and coated on the surface of the PET substrate after mixing evenly to prepare a positive electrode termination tape. Among them, the positive electrode termination tape includes a PET substrate and a rubber termination adhesive layer coated on the surface of the PET substrate, the specific amount of vinylene carbonate in the rubber termination adhesive layer is shown in Table 1, and the area of ​​the positive electrode termination tape is shown in Table 1.

[0061] (6) Preparation of lithium-ion batteries

[0062] The positive electrode sheet, separator and negative electrode sheet prepared above are wound, and a positive electrode termination tape is attached to the end of the positive electrode sheet (the area of ​​the positive electrode termination tape on both sides of the positive current collector is the same) to obtain a bare battery cell without liquid injection; the bare battery cell is placed in an outer packaging foil, and the prepared electrolyte is injected into the dried bare battery cell. After vacuum packaging, standing, formation, shaping, sorting and other processes, the required lithium-ion battery is obtained.

[0063] Table 1 Lithium ion batteries prepared in Comparative Examples 1-5 and Examples 1-7

[0064]

[0065]

[0066] Table 2 Test results of batteries obtained from comparative examples 1-5 and examples 1-7

[0067]

[0068]

[0069] The electrochemical performance of the batteries obtained in the above comparative examples and embodiments was tested, and the relevant descriptions are as follows:

[0070] 45℃ cycle experiment: The batteries obtained in the above embodiments and comparative examples were placed in a (45±2)℃ environment and left to stand for 2-3 hours. When the battery body reached (45±2)℃, the battery was charged at a 1C constant current with a cut-off current of 0.05C. After the battery was fully charged, it was left for 5 minutes and then discharged at a 0.7C constant current to a cut-off voltage of 3.0V. The highest discharge capacity of the first three cycles was recorded as the initial capacity Q. When the cycle reached 400 times, the last discharge capacity Q1 of the battery was recorded. The 400T cycled battery was disassembled to record whether lithium was deposited at the edge of the battery. The recorded results are shown in Table 2.

[0071] The calculation formula used is as follows: Capacity retention rate (%) = Q1 / Q×100%.

[0072] 70℃ high temperature storage for 60 hours experiment: The batteries obtained from the above examples and comparative examples were placed at room temperature and subjected to three charge and discharge cycle tests at a charge and discharge rate of 0.5C, and then charged to a fully charged state at a rate of 0.5C, and the highest discharge capacity Q2 and battery thickness T1 of the first three 0.5C cycles were recorded respectively. The fully charged battery was stored at 70℃ for 60 hours, and the battery thickness T2 and 0.5C discharge capacity Q3 after 60 hours were recorded. The experimental data such as the thickness change rate and capacity retention rate of the battery during high temperature storage were calculated, and the recorded results are shown in Table 2.

[0073] The calculation formula used is as follows:

[0074] Capacity retention rate (%) = Q3 / Q2×100%; Thickness change rate (%) = (T2-T1) / T1×100%

[0075] 130℃ thermal shock test: The batteries obtained in the above examples and comparative examples were heated by convection or circulating hot air oven at a starting temperature of 25±3℃, a temperature gradient of 5±2℃ / min, and the temperature was raised to 130±2℃. The test was terminated after maintaining for 60min, and the battery status results were recorded as shown in Table 2.

[0076] It can be seen from the results in Table 2 that: Through the comparative examples and embodiments, it can be seen that the battery prepared by increasing the lithium salt concentration in the electrolyte and using it in combination with the positive electrode termination tape can effectively improve the high temperature performance of the battery while solving the problem of lithium deposition at the edge of the electrode after battery cycling.

[0077] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A battery, comprising a positive electrode sheet, a negative electrode sheet, a non-aqueous electrolyte and a separator; a positive electrode sheet termination tape is provided at the paste tail of the positive electrode sheet; the non-aqueous electrolyte comprises a non-aqueous organic solvent and a lithium salt; The area of ​​the positive electrode termination tape is A cm 2 , the concentration of the lithium salt is B mol / L, the width of the positive electrode sheet is C cm, wherein, The ratio of A to B is between 2 and 20; the ratio of A to C is between 1 and 3; Wherein, a part of the positive electrode sheet termination tape covers the paste on the surface of the positive electrode current collector, and a part of the tape covers the surface of the positive electrode current collector; The area A of the positive electrode sheet termination tape refers to the area of ​​the positive electrode sheet termination tape provided on the surface of one side of the positive electrode current collector in the positive electrode sheet; The area A of the positive electrode termination tape is 3 cm 2 ~120cm 2 between ranges; The width C of the positive electrode sheet is in the range of 1 cm to 120 cm; The positive electrode sheet termination tape comprises a PET substrate and a rubber termination adhesive layer coated on the surface of the PET substrate.

2. The battery according to claim 1, wherein The concentration B of the lithium salt is 1 mol / L to 6 mol / L; Preferably, the concentration B of the lithium salt is 1.5 mol / L to 3 mol / L.

3. The battery according to any one of claims 1 to 2, wherein: The lithium salt is selected from at least one of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate.

4. The battery according to any one of claims 1 to 3, wherein: The rubber termination rubber layer includes cross-linked modified rubber, and the cross-linking agent of the cross-linked modified rubber includes vinylene carbonate.

5. The battery according to claim 4, wherein The content of the vinylene carbonate is 0.5 to 5 wt.% of the mass of the cross-linked modified rubber.

6. The battery according to any one of claims 1 to 5, wherein: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer coated on one side or both sides of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, a conductive agent and a binder.

7. The battery according to claim 6, wherein The positive electrode active material is selected from lithium cobalt oxide or lithium cobalt oxide doped and coated with two or more elements of Al, Mg, Mn, Cr, Ti and Zr.

8. The battery according to claim 6 or 7, wherein: The chemical formula of the positive electrode active material is shown below: If x What 1-y1-y2-y3-y4 AND y1 B y2 C y3 D y4 O2; Among them, 0.95≤x≤1.05, 0.01≤y1≤0.1, 0.01≤y2≤0.1, 0≤y3≤0.1, 0≤y4≤0.1, and A, B, C, and D are selected from two or more elements of Al, Mg, Mn, Cr, Ti, and Zr.

9. The battery according to any one of claims 1 to 8, wherein: The non-aqueous electrolyte further includes an electrolyte additive; The electrolyte additive also includes at least one of 1,3-propane sultone, 1,3-propylene sultone, fluoroethylene carbonate, vinyl sulfite, vinyl sulfate, lithium dioxalatoborate, lithium difluorophosphate, lithium difluorooxalatophosphate and vinyl carbonate, and the content thereof accounts for 0 to 10 wt % of the total mass of the non-aqueous electrolyte.

10. The battery according to any one of claims 1 to 9, wherein: The non-aqueous organic solvent is selected from at least one of carbonates, carboxylates and fluoroethers, wherein the carbonate is selected from one or more combinations of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate and methyl propyl carbonate; the carboxylates are selected from one or more combinations of ethyl propionate and propyl propionate; and the fluoroether is selected from 1,1,2,3-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

11. The battery according to any one of claims 1 to 10, wherein: The charging cut-off voltage of the battery is 4.45V or above.

12. The battery according to any one of claims 1 to 11, wherein: The battery is a lithium ion secondary battery.

Citation Information

Patent Citations

  • Primary lithium battery with high discharge efficiency

    CN110676458A

  • Quick-charging and safe low-temperature lithium ion battery and manufacturing method thereof

    CN111370752A

  • Wide-temperature-range high-performance primary lithium-manganese battery and preparation method thereof

    CN112186210A

  • Lithium battery anode piece structure

    CN201364922Y

  • Nonaqueous electrolyte secondary battery, and its charging method

    JP2006286337A